Dietary inflammatory potential is linked to cardiovascular disease risk burden in the US adult population. (1st August 2017) - Tyrovolas, Stefanos; Koyanagi, Ai; Kotsakis, Georgios A.; Panagiotakos, Demosthenes; Shivappa, Nitin; Wirth, Michael D.; Hébert, James R.; Haro, Josep Maria
Abstract: Background: Dietary guidelines are a key tool in the public health quiver. Single nutrients have been linked to cardiovascular diseases, but existing metrics do not capture the overall effect of diet on inflammatory diseases. The aim of this study was to examine the association between dietary inflammatory potential and cardiovascular diseases risk factors (CVD-RFs) in a nationally-representative sample of non-institutionalized US adults using data from the continuous National Health and Nutrition Examination Survey (NHANES) (2007-2012). Methods and results: A sample of 7880 non-institutionalized US adults aged ≥ 20 years provided data on dietary habits and CVD-RFs (obesity; diabetes mellitus; hypertension; hypercholesterolemia). The total number of CVD-RFs was summed for each individual to create a CVD-RF morbidity index (range 0-4) as the outcome variable, used both as ordinal and dichotomous (no CVD-RFs versus at least one CVD-RF) variables. The association between the Dietary Inflammatory Index (DII) and at least one CVD-RF was dose-dependent, with participants in the 3rd and 4th quartile of DII (i.e., more pro-inflammatory dietary habits) being 1.37 (95%CI = 1.11-1.68) and 1.50 (95%CI = 1.19-1.90) times more likely, respectively, to have at least one CVD-RF, as compared to participants in the 1st quartile of DII scores. Similar results were obtained for the ordinal logistic regression using the CVD-RF morbidity index as the outcome. Conclusions: Among US adults aged ≥ 20 years, pro-inflammatory dietary patterns, as assessed by the DII, were associated with increased odds for CVD-RFs. Dietary guidelines aimed at lowering the DII may reduce the CVD-RF burden in US adults.